Attestation : Pablo Alvaro - Tewson, Vincent
001-0138-001 Secretary's. HVT/FC/570 20th July, 1943. ATTESTATION I hereby certify that Mr. Pablo Alvaro, at present residing at 54, Mornington Terrace, London, N.W.1., of Spanish nationality, is known to me as a Spanish refugee and Vice-Chairman of the Spanish Trade Union Group in Great Britain. He has collaborated for a number of years with the International Federation of Trade Unions. I can therefore readily vouch for his good faith. Assistant Secretary. 292/946/1/138